Food Analysis - Nielsen, S. Suzanne; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
This book provides information on the techniques needed to analyze foods in laboratory experiments. All topics covered include information on the basic principles, procedures, advantages, limitations, and applications. This book is ideal for undergraduate courses in food analysis and is also an invaluable reference to professionals in the food industry. General information is provided on regulations, standards, labeling, sampling and data handling as background for chapters on specific methods to determine the chemical composition and characteristics of foods. Large, expanded sections on spectroscopy and chromatography also are included. Other methods and instrumentation such as thermal analysis, ion-selective electrodes, enzymes, and immunoassays are covered from the perspective of their use in the analysis of foods. A website with related teaching materials is accessible to instructors who adopt the textbook.
General Information -- to Food Analysis -- United States Government Regulations and International Standards Related to Food Analysis -- Nutrition Labeling -- Evaluation of Analytical Data -- Sampling and Sample Preparation -- Compositional Analysis of Foods -- Moisture and Total Solids Analysis -- Ash Analysis -- Fat Analysis -- Protein Analysis -- Carbohydrate Analysis -- Vitamin Analysis -- Traditional Methods for Mineral Analysis -- Chemical Properties and Characteristics of Foods -- pH and Titratable Acidity -- Fat Characterization -- Protein Separation and Characterization Procedures -- Application of Enzymes in Food Analysis -- Immunoassays -- Analysis of Food Contaminants, Residues, and Chemical Constituents of Concern -- Analysis for Extraneous Matter -- Determination of Oxygen Demand -- Spectroscopy -- Basic Principles of Spectroscopy -- Ultraviolet, Visible, and Fluorescence Spectroscopy -- Infrared Spectroscopy -- Atomic Absorption Spectroscopy, Atomic Emission Spectroscopy, and Inductively Coupled Plasma-Mass Spectrometry -- Nuclear Magnetic Resonance -- Mass Spectrometry -- Chromatography -- Basic Principles of Chromatography -- High-Performance Liquid Chromatography -- Gas Chromatography -- Physical Properties of Foods -- Rheological Principles for Food Analysis -- Thermal Analysis -- Color Analysis.
Keywords: Chemistry; Food science; Chemical engineering; Chemistry; Food Science; Industrial Chemistry/Chemical Engineering